Big Nate : say good-bye to Dork City - Peirce, Lincoln (Peirce, Lincoln. Big Nate (Comic strip), 2015)
"Can Nate Wright get any cooler? Not according to Nate himself. He's already P.S. 38's rockin'est drummer, finest poet (check out his haiku about Brazil nuts), and deepest thinker--in his own mind. But does Nate have what it takes to hang with Marcus, leader of the school's most notorious posse? Or will he decide that being cool isn't all it's cracked up to be?"--